EVALUASI KINERJA JARINGAN SYARAF TIRUAN PADA PERAMALAN KONSUMSI LISTRIK KELOMPOK TARIF RUMAH TANGGA - Eka N. Kencana, I Putu; Jayanegara, Ketut (Jurnal Matematika; Vol 2 No 1 (2012), 2012)
Many methods have been applied in forecasting technics, varied from Statistical Forecasting Methods (SFM) or Mathematical Modelling and Forecasting Methods (MMFM) to Artificial Neural Methods (ANM). This research aimed to implement and evaluate performance of Artificial Neural Network (ANN), one method in ANM group; for forecasting electricity consumption by household in Province of Bali. This research used electricity consumption data from January 2001 to December 2009 as basis for network’s training and validating its result. The actual data from January to December 2010 is used to evaluate the performance of network prediction. Research shows the Mean Absolute Prediction Error (MAPE) of the ANN’s prediction is 7,56%.
Keywords: forecasting, electricity consumption, artificial neural network, MAPE